The films of Antoinetta Angelidi - Bouska, Penny; Petridis, Sotiris, 1990- (ReFocus: the international directors series., 2023)
"Angelidi's work has become synonymous with Greek Experimental Cinema, while her films and her theoretical writings have been the subject of numerous film courses, critical essays and retrospectives. The inversion and juxtaposition of codes, as well as the dream-mechanism and the uncanny, comprise her main creative strategies. The complexity of cinematic heterogeneity and the narrative multiplicity of different filmic elements which characterize her work are examined in depth in this edited collection dedicated to Antoinetta Angelidi's oeuvre."--